A New Hypothesis on Anxiety, Sleep Insufficiency, and Viral Infections; Reciprocal Links to Consider in Today's “World vs. COVID-19” Endeavors - Nami, Mohammad; Mehrabi, Samrad; Kamali, Ali-Mohammad; Kazemiha, Milad; Carvalho, Jose; Derman, Sabri; Lakey-Betia, Johant; Vasquez, Velmarini; Kosagisharaf, Rao (Frontiers in Psychiatry, 2020)
In today's ever-growing concerns about the coronavirus disease (COVID-19) pandemic, many experience sleep insufficiencies, such as difficulty falling or staying asleep, sleep-related behavioral symptoms, and out-of-phase circadian rhythmicity despite the lack of history of earlier such symptoms. Meanwhile, the disruption in sleep bioparameters is experienced more in people with a history of sleep disorders. The behavioral sleep disorders in the current situations are prevalent given the today's amount of anxiety everyone is feeling about COVID-19. On the other hand, evidences indicated that the cross-link between impaired sleep efficiency and disrupted innate immunity makes people susceptible to viral infections. The present brief review highlights the links between psychosocial stress, sleep insufficiency, and susceptibility to viral infections in relevance to COVID-19 situation. The stress management measures, including addressing sleep-related disorders and sleep hygiene, will have a notable impact by harnessing immune response and thus reducing the susceptibility to viral infections.